Pemikiran jemaat Ahmadiyyah dalam The holy Qur’an with translation and commentary in Indonesia: Kajian terhadap Mirza Basyiruddin Mahmud Ahmad dan pengruhnya di Sumatera Utara / Andi Putra Ishak - Andi Putra, Ishak (2017)
This is a study of the ideology Jemaat Ahmadiyyah in the book of tafsir The Holy Qur’an With Translation And Commentary In Indonesia, a study about Mirza Basyiruddin Mahmud Ahmad and his influence in North Sumatra. This ideology has been disseminated in Indonesia, including North Sumatra without the permission and review of the Indonesian Islamic Religious Department and it could threaten to deviate the faith of Indonesian Muslims. The study aimed to explain the history of Jemaat Ahmadiyyah in North Sumatera and to shed light upon a tafsir figure of Jemaat Ahmadiyyah and his book of tafsir. The main focus of the study was to explore and analyze Basyiruddin's thinking in the tafsir, besides attempting to assess the influence of his thinking in North Sumatera. To achieve these objectives, the researcher conducted library research and field research via interviews and observation. The analysis in this study showed that the Jemaat Ahmadiyyah had entered North Sumatra before Indonesia achieved its independence. Basyiruddin himself put in the efforts in spreading the teaching who interpreted the qur'an completely trough The Holy Qur’an With Translation And Commentary In Indonesia. The findings of this study showed that there were some odd thoughts in the book, particularly those related to the divinity, prophethood, Ghulam Ahmad’s claim of prophethood, nasikh mansukh and the issues of miracles. The odd thoughts resulted from Basyiruddin’s failure to adhere to the required method of interpreting of the qur'an, where his method was contradictory with the Arabic language, the hadith of prophet Muhammad SAW and the views of renown tafsir scholars. This study further revealed that Basyiruddin's ideology reached North Sumatra through preaching activities, publishing and distribution of his tafsir book. The ideology was subsequently developed by members of Jemaat Ahmadiyyah by establishing their branches in North Sumatra, namely in Medan, Rempah Baru and Berastagi. However, the influence brought about by his ideology was reputed by the majority of the community in North Sumatera, because of the firm belief in religion among the local muslims and his vagueness in the interpretation of qur’an.